2016
DOI: 10.1111/jon.12354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Glioma Response to Radiotherapy Using Multiple MRI Biomarkers with Manual and Semiautomated Segmentation Algorithms

Abstract: Background and Purpose Multi-modality MRI can provide complementary information in the assessment of brain tumors. We aimed to segment tumor in amide proton transfer-weighted (APTw) images and to investigate multi-parametric MRI biomarkers for the assessment of glioma response to radiotherapy. For tumor extraction, we evaluated a semi-automated segmentation method based on region of interest (ROI) results by comparing it with the manual segmentation method. Methods Thirteen nude rats injected with U87 tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
1
6
1
Order By: Relevance
“…As interobserver concordance is dependent on extent of sampling [ 88 ], the method of segmentation should be clearly recorded, for example, whether whole tumour or selected slices are segmented, and whether necrotic or cystic areas are excluded. A manual, semi-automated or automated method could also introduce variability in the measurement [ 89 ] and should be standardised.…”
Section: Data Storage and Analysismentioning
confidence: 99%
“…As interobserver concordance is dependent on extent of sampling [ 88 ], the method of segmentation should be clearly recorded, for example, whether whole tumour or selected slices are segmented, and whether necrotic or cystic areas are excluded. A manual, semi-automated or automated method could also introduce variability in the measurement [ 89 ] and should be standardised.…”
Section: Data Storage and Analysismentioning
confidence: 99%
“…1 In vivo APT effect in the cancerous tissue has been largely attributed to endogenous cellular protein and peptide content change, which is valuable in tumor grading [2][3][4][5] and prediction of response to treatments. [6][7][8][9][10][11][12] Magnetization transfer (MT) asymmetry (MTR asym ) analysis has been widely used to measure in vivo APT effect because it is simple to calculate yet reasonably corrects the direct radiofrequency (RF) saturation of the bulk water signal (i.e., direct water saturation [DWS]). However, it has been recognized that in vivo MTR asym is complex.…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the accuracy of tumour localization and delineation, a semiautomatic segmentation method was evaluated to provide more reliable MR biomarkers. 32 Comparison between manual and semiautomatic analysis revealed lower intra-and interobserver variability using the semiautomatic methods, improving the accuracy of multiparametric MR. This research group also compared their multiparametric MR approach to contrast-enhanced ultrasound imaging (CEUS) and observed that several CEUS-based metrics correlated well with MR-based metrics.…”
Section: Mr-guided Rt In Animal Models Of Glioblastomamentioning
confidence: 92%
“…31 Pre-clinical, these more advanced MR techniques were used by the MR research group at John Hopkins University for the assessment of response to RT in a rat model of GB. [32][33][34] Hong et al 34 performed longitudinal quantitative multiparametric MRI, in addition to standard T 2 weighted MR. The quantitative MR sequences included T 1 relaxometry, T 2 relaxometry, diffusion-weighted imaging (DWI), arterial spin labelling and chemical exchange-dependent saturation transfer (CEST) techniques.…”
Section: Mr-guided Rt In Animal Models Of Glioblastomamentioning
confidence: 99%